Fluid dynamics and smear layer removal evaluation between EndoVac, modified apical negative pressure and positive pressure irrigation techniques - Wan Abdul Rahman, Wan Nur Farhana (2024)
Negative pressure irrigation system can deliver irrigant to the most apical areas and eliminate vapour lock, resulting in an improved smear layer (SL) removal. However, the current negative pressure irrigation system EndoVac produces the lowest wall shear stress (WSS). WSS influences the detachment of SL and biofilms from the root canal wall. This study aimed to evaluate the fluid dynamics and SL removal between EndoVac, a novel system-modified apical negative pressure (mANP), and SV positive pressure techniques. (Phase 1): A simulated 3-dimensional (3D) root canal model and three types of needles (EndoVac, mANP, and SV-positive pressure) were simulated. Model parameters and computer solution were set to analyse the WSS, apical pressure, and streamlines using computational fluid dynamics (CFD). (Phase 2): SL removal was investigated, which consists of 60 single-rooted extracted permanent lower premolars. The root canal was prepared up to F4 ProTaper size before being randomly divided into three groups: Group 1 (EndoVac), Group 2 (mANP), and Group 3 (SV). The samples were vertically split into half and observed under a scanning electron microscope (SEM). In CFD analysis, the mANP showed the highest average WSS (11.06 Pa) compared to SV (10.72 Pa) and EndoVac (10.48 Pa). Conversely, the SV positive pressure method revealed limited streamlines beyond the needle tip and positive apical pressure. In SEM evaluation, the mANP demonstrated superior SL removal compared to the other groups. There were significant differences in irrigation dynamics pattern in CFD analysis and the SL removal between the three groups using Fisher's exact test. In conclusion, this study revealed that different irrigation systems and needle designs affect the fluid dynamics pattern and magnitude. The mANP revealed the highest average WSS magnitude and the cleanest SL removal compared to the EndoVac and SV positive pressure technique. Thus, this proves there is a direct correlation between average WSS magnitude and SL removal.